Visceral Abdominal and Subfascial Femoral Adipose Tissue Have Opposite Associations with Liver Fat in Overweight and Obese Premenopausal Caucasian Women. (22nd September 2011) - Rocha, Paulo M.; Barata, José T.; Minderico, Cláudia S.; Silva, Analiza M.; Teixeira, Pedro J.; Sardinha, Luís B.
Abstract : Abdominal obesity has been associated with liver fat storage. However, the relationships between other body composition depots and metabolic syndrome features with hepatic fat are still unclear. We examined abdominal and thigh adipose tissue (AT) compartments associations with liver fat in 140 overweight and obese premenopausal Caucasian women. Blood lipids and, proinflammatory and atherothrombotic markers associations with hepatic fat were also analyzed. A larger visceral AT (VAT) was related with liver fat (P < 0.05 ). Contrarily, thigh subfascial AT was inversely related to liver fat (P < 0.05 ). Increased fasting insulin, triglycerides, PAI-1 concentrations, and a higher total-cholesterol/HDL-cholesterol ratio were also associated with hepatic fat, even after adjustment for VAT (P < 0.05 ). Thigh subfascial adiposity was inversely associated with liver fat, suggesting a potential preventive role against ectopic fat storage in overweight and obese women. These results reinforce the contribution of an abdominal obesity phenotype associated with a diabetogenic and atherothrombotic profile to liver lipotoxicity.